Synthesis and biological evaluation of new 2-(4-fluorophenyl) imidazol-5-ones as anticancer agents - Yasmin A. Abo-Elanwar, Amany S. Mostafa, Magda A. A. El-Sayed , Magda N. A. Nasr (Journal of Applied Pharmaceutical Science, 2019)
Two series of imidazolones were designed, synthesized, and evaluated for their anticancer activity against four cancer cell lines: Hela, MCF-7, PC3, and HCT-116, where four compounds 6, 25, 26, and 29 showed good potency against the whole panel. Compound 30 showed a cytotoxic effect against PC3 cell lines compared to that of the standard doxorubicin with IC50 = 8.15µM, while compounds 4 and 18 showed moderate activity with IC50 range of 10.58–11.45 µM. Enzyme inhibition assay was implemented against CDK2A and VEGFR-2; where varied activities were obtained. Compound 6 exhibited the highest inhibitory activity against VEGFR-2 with an IC50 value of 67 nM and moderate inhibition against CDK2A, while compound 26 achieved the best result against CDK2A with an IC50 value of 0.66 µM.
Keywords: Imidazlone, chalcones, anticancer, VEGFR-2, CDK2A.